2021
DOI: 10.1155/2021/6621894
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Radiomics Nomogram for Prognosis Prediction of Patients with Acute Paraquat Poisoning: A Retrospective Cohort Study

Abstract: Objective. To evaluate the efficiency of a radiomics model in predicting the prognosis of patients with acute paraquat poisoning (APP). Materials and Methods. Chest computed tomography images and clinical data of 80 patients with APP were obtained from November 2014 to October 2017, which were randomly assigned to a primary group and a validation group by a ratio of 7 : 3, and then the radiomics features were extracted from the whole lung. Principal component analysis (PCA) and least absolute shrinkage and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…1); among them, 360/724 patients (49.7%) died. In terms of demographics, there were 325/724 (44.9%) males, with a median age of 33 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) years. Among 506/724 patients in the training group, 44.1% were male, with a median age of 29 years, and 253/506 (50%) patients died.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…1); among them, 360/724 patients (49.7%) died. In terms of demographics, there were 325/724 (44.9%) males, with a median age of 33 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) years. Among 506/724 patients in the training group, 44.1% were male, with a median age of 29 years, and 253/506 (50%) patients died.…”
Section: Patientsmentioning
confidence: 99%
“…Among 506/724 patients in the training group, 44.1% were male, with a median age of 29 years, and 253/506 (50%) patients died. Of the 218/724 patients in the validation group, 46.8% were male, with a median age of 31 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) years, and 107/218 (49.1%) patients died. No statistical significant differences were observed between the two groups (P > 0.05) (Table 1).…”
Section: Patientsmentioning
confidence: 99%
“… 8 Previous literature also revealed that liver and renal dysfunction, serum anion gap above 25.5 mmoL/L, and computerized tomography of the thorax were predictors of outcomes in PP. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Despite its widespread use as an herbicide, PQ's high toxicity and limited detoxi cation options have resulted in PQ poisoning becoming a major public health concern [2]. Numerous scholars have conducted studies on APP prediction models [3][4][5][6][7][8][9][10]. For instance, Chen et al utilized Support Vector Machine (SVM) to predict the prognosis of 79 APP patients using routine blood indices [7].…”
Section: Introductionmentioning
confidence: 99%